Transplanting fecal material from wild‐type mice fed black raspberries alters the immune system of recipient mice. Issue 3 (5th August 2020) - Huang, Yi‐Wen; Pan, Pan; Echeveste, Carla Elena; Wang, Hsin‐Tzu; Oshima, Kiyoko; Lin, Chien‐Wei; Yearsley, Martha; Xiao, Jianbo; Chen, Jiebiao; Sun, Chongde; Yu, Jianhua; Wang, Li‐Shu
Abstract: By constantly stimulating intestinal immunity, gut microbes play important regulatory roles, and their possible involvement in human physical and mental disorders beyond intestinal diseases suggests the importance of maintaining homeostasis in the gut microbiota. Both transplantation of fecal microbiota and dietary interventions have been shown to restore microbial homeostasis in recipients. In the current study with wild‐type mice, we combined these two approaches to determine if transplanting fecal material from mice fed black raspberries (BRB, 5%) altered recipients' immune system. The donors received a control or 5% BRB diet, and fecal transplantation was performed every other day 15 times into recipients fed control diet. Afterward, we used flow cytometry to analyze populations of CD3 + T, CD4 + T, CD8 + T cells, and NK cells among bone marrow cells, splenocytes, and peripheral blood mononuclear cells (PBMCs) collected from the recipients. We found that BRB‐fecal material that contained both fecal microbiota and their metabolites increased NK cell populations among bone marrow cells, splenocytes, and PBMCs, and raised levels of CD8 + T cells in splenocytes. Our findings suggest that fecal transplantation can modulate the immune system and might therefore be valuable for managing a range of physical and mental disorders. Abstract :